The Effects of Marketing Communication on Church Growth in Ghana - Acheampong, V. (University of Ghana, 2014)
In this era of intense competition, especially amongst churches, the yardstick for measuring success depends on the extent of awareness creation, persuasion and informing customers of the existence of offerings and this has resulted in several marketing communications tools being employed by churches to help them succeed in this kind of competition. This study sought to explore the application of marketing communication by churches in Ghana. The study adopted a mixed method approach. An in-depth personal interview was conducted by purposively sampling 12 church administrators which enabled the researcher to identify the marketing communication tools that churches in Ghana employ. The convenience random sampling technique was used to select 400 church attendees from the Adenta Municipality who completed questionnaires. The recorded interviews were transcribed verbatim and subjected to thematic analysis. Data collected from the church attendees were coded into the SPSS and analysed using descriptive statistics, Factor Analysis, multiple regression, and Analysis of Variance ‘ANOVA’. Though the effects of marketing communication tools differed among respondents in terms of age groups, denominations and educational levels, this study found that there were no significant relationships between advertising, publicity/public relations and church growth. However, there was a significant relationship between personal selling, direct marketing, sales promotion and church growth. Therefore the study concludes that personal selling, direct marketing and sales promotion had influence on Ghanaians’ choice of church.
Thesis(MPHIL)-University of Ghana, 2014
Keywords: Marketing Communication; Church Growth